Formulation and characterization of celecoxib-loaded fractionated medium chain triglycerides oil based nanoemulgel - Hairul, Nuriana Munirah; Anuar, Nor Khaizan; Zulfakar, Mohd Hanif; Salim, Norazlinaliza; Ibrahim, Salizatul Ilyana (Malaysian Institute of Chemistry, 2024)
Celecoxib (CXB) is a lipophilic drug with limited solubility in water and reduced oral bioavailability. Nanoemulgel (NEG) is a promising transdermal delivery system that improves the solubility and bioavailability of poorly water-soluble drugs compared to oral administration. Therefore, this study aimed to develop and characterize a transdermal NEG formulation for CXB, utilizing fractionated medium-chain triglycerides (FMCTs) oils as carrier oils. FMCTs oils, derived from palm kernel oil (Elaeis guineensis), are known for their ability to enhance the solubility of lipophilic drugs, making them an appealing choice for this application. The study began by selecting carrier oils - caprylic capric triglyceride (MCT) and a blend with palm kernel olein (PKOlein) based on solubility tests. Phase diagrams were constructed to determine the optimal concentrations for formulating the nanoemulsion (NE). Various NE formulations were prepared using the low-energy emulsification method, followed by formulating corresponding nanoemulgel (NEG) by incorporating Carbopol 940 in varying concentrations. The developed NEs and NEG exhibited the droplet size range between 26.75 and 55.87 nm with the zeta potential values within -22.47 to -38.83 mV and the PDI values less than 0.5, whereas the morphology showed a well-identified spherical particle. Two formulations named NEG-F14 0.5% and NEG-F17 0.5% were selected for further study on the drug content, EE% and in-vitro drug release. Results showed that NEG-F17 0.5% had a higher drug content (97.54%) with 83.39% of EE when compared with NEG-F15 0.5%. The drug release study shows that NEGF17 0.5% was remarkably higher as compared to NEG-F14 0.5%, due to the presence of PKOlein in nanoemulsion which improve the solubility, decrease particle size, thus increasing the penetration of CXB. These findings collectively suggest that the developed NEs and NEGs offered desirable attributes for their potential in transdermal drug delivery.